Hybride tilbageblik - Tanderup, Sara (Passage - Tidsskrift for litteratur og kritik, 2012)
Sara Tanderup: "Hybride tilbageblik - Montage, fotografi og mediebevidsthed i den moderne eksperimenterende erindringsroman" Abstract Sara Tanderup: “Hybrid Memories: Montage, Media and Photography in Modern, Visual Memory-Novels” The article focuses on intermediality as a strategy of representing memory, trauma and loss in contemporary literature. Analysing works by Alexander Kluge, W.G. Sebald, Aleksandar Hemon and Jonathan Safran Foer, the article examines the visual novels in a media perspective. Taking as a point of departure W.J.T. Mitchell’s theory of the relation between words and images, the article points to a tension within the genre: the visual novels, or ‘photo-novels’, seem torn between, on the one hand, a modernist tradition which is critical towards the modern culture of media and images and turns towards literature as a ‘last bastion’ of continuity and stability in relation to the past – and another tendency, which seems to embrace the other media and the new possibilities they bring for thinking, telling and remembering in words and images.